A responsabilidade civil no direito ambiental: subsídios para a responsabilização pós-consumo dos fabricantes de embalagens - Gewehr, Mathias Felipe (My University, 2014)
The civil liability is one of the justinian codes oldest of the law, being that its antecedents retrace Old Rome. The civil liability was inserted in the Brazilian legal system at a first moment in its subjective modality, whose elements were fixed in the action or omission, the guilt, the damage and the causal nexus. With the intensification of the industrial processes and the complexity of the relations between industries and consumers it passed to be seen under the objective modality, where it was enough to make responsible the causing agent, the existence of the damage and in the causal nexus enters this the action. The civil liability if improved until passing to be analyzed under the ambient plan, stimulated for the great ambient damages provoked by the industry against the environment. In way that currently can be said that the objective civil liability with regard to the consumer and to the environment coexists, in simultaneous way. What it is damage to the consumer, also can be damage to the environment. In this objective aspect to approach the civil liability after-consumption on the part of the manufacturers who to one time attack the environment and only provoke damages to the health and well-being of the consumer. It is defended necessity of the extension of the relation of consumption from the state intervention in the private relations and is placed in test the principle of the ambientsociofunction of this contract as form to search the responsibility after- consumption of the manufacturers. However necessary the existence of a change in the position of the consumers and of a taking of conscience on the part of the industry making with that the balance between economic activity, environment and consumption is guaranteed, to start to adopt the ambientsocioconscience that discloses the sustainable development and assures the healthy quality of life to the presents and futures generations.
A responsabilidade civil é um dos institutos mais antigos do direito, sendo que seus antecedentes remontam a Roma Antiga. A responsabilidade civil foi inserida no ordenamento jurídico brasileiro em um primeiro momento em sua modalidade subjetiva, cujos elementos estavam fixados na ação ou omissão, na culpa, no dano e no nexo de causalidade. Com a intensificação dos processos industriais e a complexidade das relações entre indústrias e consumidores passou a ser vista sob a modalidade objetiva, em que bastava para responsabilizar o agente causador, a existência do dano e no nexo causal entre este a ação. A responsabilidade civil se aprimorou até passar a ser analisada sob o plano ambiental, impulsionada pelos grandes danos ambientais provocados pela indústria contra o meio ambiente. De modo que atualmente pode-se dizer que coexiste a responsabilidade civil objetiva com relação ao consumidor e ao meio ambiente, de maneira simultânea. O que é dano ao consumidor, também pode ser dano ao meio ambiente. Neste aspecto objetiva-se abordar a responsabilidade civil pós-consumo por parte dos fabricantes que a um só tempo agridem o meio ambiente e provocam danos à saúde e ao bem-estar do consumidor. Defende-se a necessidade da extensão da relação de consumo a partir da intervenção estatal nas relações privadas e coloca-se em teste o princípio da função social e ambiental deste contrato como forma de buscar a responsabilidade pós-consumo dos fabricantes. Todavia, necessária a existência de uma mudança na postura dos consumidores e de uma tomada de consciência por parte da indústria para fazer com que seja garantido o equilíbrio entre atividade econômica, meio ambiente e consumo, para passar a adotar a consciência socioambiental que revele o desenvolvimento sustentável e assegure a sadia qualidade de vida às presentes e futuras gerações.
Keywords: Direito civil; Responsabilidade civil; Direito ambiental; Fabricantes; Responsabilidade pós-consumo; Civil responsability; Environmental law; Manufacture; Responsability after-consume